Robinia pseudoacacia sand stabilizer: its sand fixation effects and mechanical properties - Ren, Tingjie; Gao, Yong; Yuan, Limin; Zhao, Chen (Frontiers in Environmental Science, 2024)
To explore the sand stabilization effects of Robinia pseudoacacia sand stabilizer, a series of spraying experiments were conducted using different dry matter dosages (0.5, 1, 2, 3, 4, and 5g/m²). The sand stabilization effects, mechanical properties, and wind erosion conditions of the stabilizer were measured. The results show that:(1) After spraying the sand stabilizer, a consolidated layer with a thickness of 1~14 mm is formed on the sand surface.The average compressive strength increased by 206.21% compared to the control group (0g/m 2 ), and wind erosion was reduced by 35.47% to 65.92%. (2) The compressive strength of the consolidation layer positively correlated with the dosage and thickness (the depth or the vertical dimension of the consolidation layer ) (P＜0.05), and inversely correlated with wind erosion and total porosity. As the dosage increased, the total porosity decreased, the thickness of the consolidation layer increased, and the compressive strength increased even more, making the material more resistant to wind erosion.